2021
DOI: 10.36877/pmmb.a0000195
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequence of bioactive streptomycete derived from mangrove forest in Malaysia, Streptomyces sp. MUSC 14

Abstract: The contribution of streptomycetes to human health is undeniably important and significant, given that these filamentous microbes can produce interesting compounds that can be used to cure deadly infections and even cancer. Isolated from the east coast of Peninsular Malaysia, Streptomyces sp. MUSC 14 has shown significant antioxidant capacity. The current study explores the genomic potential of MUSC 14 via a genome mining approach. The genome size of MUSC 14 is 10,274,825 bp with G + C content of 71.3 %. AntiS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 69 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…Certain unique strains thrive in extreme niches, such as the hypersaline bacteria and Streptomyces spp. isolated from mangrove soils are excellent sources of exogenous enzymes that work efficiently under extreme conditions [104,[400][401][402][403][404] . These extracellular enzymes supplemented by probiotics may function optimally at broader pH and salinity range, thereby extending the period of enzymatic digestion to facilitate more efficient hydrolysis of substrates [405,406] .…”
Section: Increasing the Digestive Enzyme Activitymentioning
confidence: 99%
“…Certain unique strains thrive in extreme niches, such as the hypersaline bacteria and Streptomyces spp. isolated from mangrove soils are excellent sources of exogenous enzymes that work efficiently under extreme conditions [104,[400][401][402][403][404] . These extracellular enzymes supplemented by probiotics may function optimally at broader pH and salinity range, thereby extending the period of enzymatic digestion to facilitate more efficient hydrolysis of substrates [405,406] .…”
Section: Increasing the Digestive Enzyme Activitymentioning
confidence: 99%
“…They are abundant in nature and have been frequently isolated from various sources such as soils, mangroves, and marine environments [76][77][78][79][80][81] . The use of streptomycetes as a probiotic has widely studied due to their ability to produce bioactive secondary metabolites during their life cycle [82][83][84][85][86][87][88] . Moreover, Streptomyces sp.…”
Section: Data Descriptionmentioning
confidence: 99%
“…In recent years, the uprising of various next-generation sequencing (NGS) platforms has revolutionized the field of natural product discovery, where the rapidly expanding microbial genomic and metagenomic datasets unravel a vast number of biosynthetic gene clusters that encode a lot more natural products than what has been characterized to date [48]. For instance, recent advances in genome mining have revealed that Streptomyces genomes contain numerous previously unknown cryptic biosynthetic clusters, suggesting that Streptomyces genomes remain a valuable resource for novel drug discovery [49,50]. Given that the unparallel contribution of Streptomyces bacteria to human health is a treasure trove of antibacterial agents [51], there is an increasing trend of studies that show renewed interest in the potential of Streptomyces bacteria in the production of antibiofilm compounds.…”
Section: Streptomyces Sp a Valuable Source For Anti-mrsa Biofilm Agentsmentioning
confidence: 99%